2011
DOI: 10.1098/rstb.2011.0128
|View full text |Cite
|
Sign up to set email alerts
|

The sense of touch in the star-nosed mole: from mechanoreceptors to the brain

Abstract: Star-nosed moles are somatosensory specialists that explore their environment with 22 appendages that ring their nostrils. The appendages are covered with sensory domes called Eimer's organs. Each organ is associated with a Merkel cell -neurite complex, a lamellated corpuscle, and a series of 5-10 free nerve endings that form a circle of terminal swellings. Anatomy and electrophysiological recordings suggest that Eimer's organs detect small shapes and textures. There are parallels between the organization of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 54 publications
0
31
0
2
Order By: Relevance
“…Adult star-nosed moles C. cristata (N=14, both males and females) were obtained from Vanderbilt University after being collected in Pennsylvannia under permit no. COL00087 (for details, see [46]). Animals selected for the study were of different sizes and weights (typical adult individuals are 15-20 cm long and weigh about 55 g; no systematic interindividual differences were found although the immunostaining tended to be less consistent than in mice).…”
Section: Animalsmentioning
confidence: 99%
“…Adult star-nosed moles C. cristata (N=14, both males and females) were obtained from Vanderbilt University after being collected in Pennsylvannia under permit no. COL00087 (for details, see [46]). Animals selected for the study were of different sizes and weights (typical adult individuals are 15-20 cm long and weigh about 55 g; no systematic interindividual differences were found although the immunostaining tended to be less consistent than in mice).…”
Section: Animalsmentioning
confidence: 99%
“…Moving to Mammalia, the article by Catania [34] considers an unusual but fascinating tactile specialist the star-nosed mole, Condylura cristata. The study of highly-specialized systems often allows better insight into more generalized ones, as a striking feature that is highly noticeable in the specialist may reflect a general but less obvious trend in its less remarkable relatives.…”
Section: Contents Of Theme Issuementioning
confidence: 99%
“…Both species have evolved a well-developed somatosensory system and a rudimentary visual system in order to occupy a subterranean niche [Catania, 1999[Catania, , 2011Catania and Remple, 2002;Crish et al, 2006;Henry et al, 2006]. It has been suggested that these animals show a distinct pattern of expression of the molecular marker zebrin II (ZII, also known as aldolase C) [Ahn et al, 1994] in the cerebellum [Marzban et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%